How is the Compliance of Micro, Small and Medium Taxpayers (Case Study on MSME in the City of Mataram) - Sofhia, Sofhia; Husnaini, Wahidatul (East Asian Journal of Multidisciplinary Research, 2024)
This study aims to analyze in depth how taxpayer compliance in fulfilling tax obligations in the era of digitalization. This study uses qualitative with a case study approach. Researchers conduct data collection techniques through interviews (semi-structured), observation, and documentation. 9 MSME informants and two large business informants were selected using purposive sampling. The study results show that 3 out of 9 MSMEs remain compliant despite experiencing difficulties operating digital electronic systems by utilizing available services. Meanwhile, one MSME was identified as non-compliant because they needed to understand the concept of taxation and the digital tax system. One other MSME was identified as non-compliant even though they understood the electronic tax system. The Digital Empowerment Theory is supported, which shows the need for comprehensive socialization in various business fields.